A case of Rubinstein-Taybi Syndrome with a CREB-binding protein gene mutation - Se Hee Kim; Byung Chan Lim; Jong Hee Chae; Ki Joong Kim; Yong Seung Hwang (Korean Pediatric Society, 2010)
Rubinstein-Taybi syndrome (RTS) is a congenital disorder characterized by typical facial features, broad thumbs and toes, with mental retardation. Additionally, tumors, keloids and various congenital anomalies including congenital heart defects have been reported in RTS patients. In about 50% of the patients, mutations in the CREB binding protein (CREBBP) have been found, which are understood to be associated with cell growth and proliferation. Here, we describe a typical RTS patient with Arnold-Chiari malformation. A mutation in the CREBBP gene, c.4944_4945insC, was identified by mutational analysis.